Dithiolated peptides incorporating bis(tryptophan)s for cooperative mercury(II) binding. (15th August 2021) - Ngu-Schwemlein, Maria; Merle, John; Cameron, T'ea; Witcher, Charlexia; Todd, Daniel
Graphical abstract: Highlights: Bis(indole) rings as hydrophobic shields in Hg(II)-peptide complexes is evaluated. ESI-MS and UV difference spectra indicate formation of bisthiolated Hg(II) bonds. CD spectra show signature negative CD bands corresponding to cation-π interaction. Stern-Volmer fluorescence quenching are temperature independent. Theoretical calculations show bis(indole) interactions can stabilize macrocyclic complex. Abstract: The indole side chain of tryptophan is a versatile π-donor that can participate in various types of cation-π interactions. An understanding of how it may contribute as an auxiliary binding group in mercury(II) complexes can provide valuable insights toward the design of effective chelators for optimal mercury immobilization. In this study, we investigate how the incorporation of two tryptophan residues in model dicysteinyl peptides might participate in peptide-mercury(II) complex stabilization. Two pentapeptides consisting of a Cys-Trp-Cys sequence motif containing a second tryptophan residue at the N -terminal (BT1 ) or C-terminal (BT2 ) were designed. An analogous cyclohexapeptide (BT3 ) was included to evaluate how tryptophan residues, restricted in constrained peptidic turn motifs, might take part in mercury(II) complexation. Their interactions with mercury(II) were investigated by spectroscopic methods and computational modeling. UV–vis studies indicate the formation of 1:1 dithiolated mercury(II) complex, which is corroborated by ESI-MS analysis. Spectroscopic studies reveal that the tryptophan indole group(s) in BT1 and BT3 can participate in mercury(II) cation-π interactions. Optimized 1:1 mercury(II)-BT3 structures indicate that both indole rings are very close to the mercury(II) coordination site and could stabilize it by shielding it from ligand exchange. These findings provide some useful insights toward use of aromatic donor groups as hydrophobic shields in designing more effective metal chelating agents.